Contemporary kinematics of the Ordos block, North China and its adjacent rift systems constrained by dense GPS observations. (March 2017) - Zhao, Bin; Zhang, Caihong; Wang, Dongzhen; Huang, Yong; Tan, Kai; Du, Ruilin; Liu, Jingnan
Highlights: Detailed slip rates of graben-bounding faults surrounding the Ordos block are obtained from dense GPS observation. Both the Daihai and Datong basins are experiencing extensional deformation in the north segment of the Shanxi rift. The earthquake recurrence interval in North China is usually too long to assessment of the seismic hazard. Both the Indo-Asian collision and west Pacific subduction are contributing to the extensional deformation in Ordos region. Abstract: The detailed kinematic pattern of the Ordos block, North China and its surrounding rift systems remains uncertain, mainly due to the low signal-to-noise ratio of the Global Positioning System (GPS) velocity data and the lack of GPS stations in this region. In this study, we have obtained a new and dense velocity field by processing GPS data primarily collected from the Crustal Motion Observation Network of China and from other GPS networks between 1998 and 2014. The GPS velocities within the Ordos block can be interpreted as counterclockwise rotation of the block about the Euler pole with respect to the Eurasia plate. Velocity profiles across the graben-bounding faults show relatively rapid right-lateral strike-slip motion along the Yinchuan graben, with a rate of 0.8–2.6 mm/a from north to south. In addition, a right-lateral slip rate of 1.1–1.6 mm/a is estimated along the central segment of the Shanxi rift. However, strike-slip motion is not detected along the northern and southern margins of the Ordos block. Conversely, significant extension motion is detected across the northwestern corner of the block, with a value of 1.6 mm/a, and along the northern segment of the Shanxi rift, where an extensional rate of 1.3–1.7 mm/a is measured. Both the Daihai and Datong basins are experiencing crustal extension. On the southwestern margin of the block, deformation across the compressional zone of the Liupanshan range is subtle; however, the far-field shorting rate is as high as 3.0 mm/a, implying that this region is experiencing ongoing compression. The results reveal that present-day fault slip occurs mainly along the block bounding faults, with the exception of faults along the northern and southern margins of the block. These results provide new insights into the nature of tectonic deformation around the Ordos block, and are useful for assessing the seismic activity in this region.